Light and ultrasound activated precision: a novel water-soluble BODIPY-mediated sono-photosensitizer in SPDT for breast cancer treatment - Karanlik, Ceren Can; Turkkol, Aysegul; Karanlik, Gurkan; Kolac, Umut Kerem; Caliskan, Serife Gokce; Bilgin, Mehmet Dincer; Erdogmus, Ali (NATURE PORTFOLIO, 2026)
Remarkable results have been achieved by using the synergistic effect of light and ultrasound in sono-photodynamic therapy (SPDT). This application, which has been defined as a combination treatment method in recent years, aims to increase the amount of singlet oxygen produced by sono-photosensitizers. This research aims to assess the singlet oxygen generation potential of BODIPY compounds through the utilization of the SPDT method. Motivated by this fact, we synthesized and characterized a new water-soluble BODIPY compound doped with a heavy-atom and a distyryl moiety. The singlet oxygen production capacities of the compounds were investigated both photochemically and sono-photochemically. To assess their biological performance, in vitro studies were conducted using the MDA-MB-231 breast cancer cell line. Cytotoxicity and apoptosis were determined by MTT and Annexin V-FITC/PI assays, while ROS generation was detected using DHE staining under confocal microscopy. MnSOD and GPX1 expression levels were analyzed to evaluate mitochondrial antioxidant responses. The results demonstrated that both BODIPY compounds significantly enhanced reactive oxygen species (ROS) generation and apoptosis under SPDT, accompanied by increased MnSOD and GPX1 expression. In addition, molecular docking studies were conducted to evaluate the binding interactions of the newly synthesized compounds with the EGFR target protein, providing insight into their potential as multifunctional agents with both photodynamic and molecular-targeting capabilities. Molecular docking results demonstrated that the newly synthesized compounds possess markedly higher EGFR binding affinity than cisplatin, supported by lower binding energy values and stronger active-site interactions. These findings suggest that the synthesized BODIPY derivatives act as efficient sono-photosensitizers capable of inducing ROS-mediated apoptosis, highlighting their potential as promising agents for cancer therapy. Although BODIPY derivatives are well known as photosensitizers in PDT, their potential as sono-photosensitizers in SPDT has been rarely explored. This study therefore addresses an important gap by assessing the SPDT efficacy of newly synthesized water-soluble BODIPY derivatives in MDA-MB-231 cells.
Keywords: BODIPY; Combination therapy; SPDT; Breast cancer; PHOTODYNAMIC THERAPY; DERIVATIVES; DESIGN; Science & Technology - Other Topics